Perfusion reduces bispecific antibody aggregation via mitigating mitochondrial dysfunction-induced glutathione oxidation and ER stress in CHO cells - Pritam Sinharoy (Nature Portfolio, 2020)
Abstract One major challenge observed for the expression of therapeutic bispecific antibodies (BisAbs) is high product aggregates. Aggregates increase the risk of immune responses in patients and therefore must be removed at the expense of purification yields. BisAbs contain engineered disulfide bonds, which have been demonstrated to form product aggregates, if mispaired. However, the underlying intracellular mechanisms leading to product aggregate formation remain unknown. We demonstrate that impaired glutathione regulation underlies BisAb aggregation formation in a CHO cell process. Aggregate formation was evaluated for the same clonal CHO cell line producing a BisAb using fed-batch and perfusion processes. The perfusion process produced significantly lower BisAb aggregates compared to the fed-batch process. Perfusion bioreactors attenuated mitochondrial dysfunction and ER stress resulting in a favorable intracellular redox environment as indicated by improved reduced to oxidized glutathione ratio. Conversely, mitochondrial dysfunction-induced glutathione oxidation and ER stress disrupted the intracellular redox homeostasis, leading to product aggregation in the fed-batch process. Combined, our results demonstrate that mitochondrial dysfunction and ER stress impaired glutathione regulation leading to higher product aggregates in the fed-batch process. This is the first study to utilize perfusion bioreactors as a tool to demonstrate the intracellular mechanisms underlying product aggregation formation.